2007
DOI: 10.1002/da.20207
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of escitalopram in the treatment of major depressive episodes in the presence or absence of anxiety

Abstract: This open, multicenter, prospective study in France assessed the efficacy and tolerability of escitalopram in patients with depression, with or without comorbid anxiety. Escitalopram was administered over a 12-week treatment period to 790 depressed patients, including 482 patients with at least one concomitant anxiety disorder. The study was completed by 649 patients. At baseline, the mean Montgomery-Asberg Depression Rating Scale (MADRS) total score was 31.5 and decreased to 12.4 at end point (last observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…This was confirmed in later analyses [63]. In addition, patients with comorbid anxiety have been described by Olié et al, who assessed the efficacy and tolerability of escitalopram in patients with depression, with or without comorbid anxiety [64]. Escitalopram was administered over a 12-week treatment Drug Profile Höschl & Švestka period to 790 depressed patients (649 completed), including 482 patients with at least one concomitant anxiety disorder.…”
Section: Anxiety In Depressive Disordersmentioning
confidence: 80%
“…This was confirmed in later analyses [63]. In addition, patients with comorbid anxiety have been described by Olié et al, who assessed the efficacy and tolerability of escitalopram in patients with depression, with or without comorbid anxiety [64]. Escitalopram was administered over a 12-week treatment Drug Profile Höschl & Švestka period to 790 depressed patients (649 completed), including 482 patients with at least one concomitant anxiety disorder.…”
Section: Anxiety In Depressive Disordersmentioning
confidence: 80%
“…Clinicians may also consider interventions designed towards general NA symptoms for cases of isolated affective disorders to potentially prevent development of future disorders as it has been shown that an anxiety disorder for example often precedes a mood disorder (Belzer and Schneier 2004). In cases of comorbid anxiety and mood disorders, clinicians may also target the nonspecific NA symptoms to improve risk of relapse (Woody et al 1998) and pharmacological treatments are considered a frontline treatment option (Gorman 1996;Olié et al 2007). With regards to the DASS-21, the clinical implications are also that this brief measure could be used as a valid screening questionnaire to identify adolescents reporting symptoms unique to depressive or anxiogenic syndromes and general NA.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of exclusion criteria for patients in randomised clinical trials of major depressive disorder, such as comorbid anxiety and a range of concomitant medication, so the results from these analyses may not generalise to treatment in natural practice. Nevertheless, a good treatment effect has been reported in depressed patients with a high level of comorbid anxiety in a randomised controlled trial 29 , and in a setting with fewer inclusion restrictions 30 .…”
Section: Discussionmentioning
confidence: 99%